Expectations Models of Asset Prices: A Survey of Theory - Leroy, Stephen F. (Journal of Finance, 1982)
This paper identifies restrictions on preferences under which various classes of “expectations” theories of asset prices—i.e., uncertainty models of asset prices which coincide with the corresponding certainty theory except that expected future prices replace actual future prices—are valid. Major classes of expectations models surveyed are martingale models, the expectations hypothesis of the term structure of interest rates, and models of exhaustible resources and futures markets. In each case the required restriction is related to the assumptiono f risk—neutrality, but the precise nature of the required restriction is shown to differ significantly among the various classes of expectations theories.